Preparation of Sn/Mn loaded steel slag zeolite particle electrode and its removal effect on rhodamine B(RhB). (October 2020) - Zhang, Zhijie; Feng, Yan; Liu, Na; Zhao, Youheng; Wang, Xinwei; Yang, Shumin; Long, Yingying; Qiu, Liping
Abstract: A large amount of steel slag has not been effectively used, seriously polluting the environment. Based on the idea of waste control, steel slag was applied to the preparation of particle electrode for the first time. And Sn/Mn loaded steel slag zeolite particle electrode was prepared and used in a three-dimensional electrocatalytic system (TDE) for rhodamine B (RhB) degradation. The particle electrode was also characterized by X-ray fluorescence spectrum (XRF), scanning electron microscope (SEM) and X-ray diffraction (XRD). The results showed that (1) Sn/Mn loaded steel slag zeolite particle electrode was manufactured with the Sn/Mn ratio (2:1); (2) The physical and chemical characterization of Sn/Mn loaded steel slag zeolite particle electrode confirmed that it was a good particle electrode for the degradation of organics; (3) When the starting concentration of RhB is 10 mg/L, the degradation rate of RhB in the TDE reached 95.0 % at the optimal sintering conditions, such as the current 0.5 A, electrolyte 0.125 mol/L and anode below. The findings suggest that Sn/Mn loaded steel slag zeolite particle is a cheap and efficient method for degradation of dye wastewater. At the same time, it also shows that steel slag has great application potential in TDE system, which provides a new way to utilize solid waste to treat refractory organics. Highlights: Sn/Mn loaded steel slag zeolite particle electrodes were prepared from steel slag. RhB removal rate was significantly influenced by preparation conditions. The single factor experiments were explored to removal RhB in TDE. Particle electrode had high degradation efficiency for RhB.